1988
DOI: 10.1007/bf00054986
|View full text |Cite
|
Sign up to set email alerts
|

Multiple action sites for photosystem II herbicides as revealed by delayed fluorescence

Abstract: DCMU (3-(3,4-dichlorophenyl)-1,1-dimethylurea) at concentrations higher than 10 μM suppresses the second time range delayed fluorescence (DF) of pea chloroplasts, due to inhibition of the oxidizing side of photosystem II (PS II). The inhibition of the reducing side of PS II resulting in the suppression of millisecond DF takes place at much lower (∼0.01 μM) DCMU concentrations. The variation in the herbicide-affinities of the reducing and oxidizing sides of PS II is not the same for DCMU and phenol-type herbici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

1990
1990
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…A low-affinity site for atrazine has also been identified on the basis of an antibodybinding analysis (128). Furthermore, it has been suggested that a second site of herbicide action is located on the donor side of the PS II complex (131)(132)(133)(134).…”
Section: Discussionmentioning
confidence: 99%
“…A low-affinity site for atrazine has also been identified on the basis of an antibodybinding analysis (128). Furthermore, it has been suggested that a second site of herbicide action is located on the donor side of the PS II complex (131)(132)(133)(134).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, radioactively labelled herbicides were originally used to tag the D1 protein and identify it as the location of the QB site (see Biihman et al 1987). It is thought that the inhibitor molecule binds at or close to the QB site in competition with PQ binding, although recent evidence suggests that there may be two herbicide binding sites in the Reaction Core (Hsu et al 1986, Giardi ,et al 1988, Vasil'ev et al 1988). It is thought that the inhibitor molecule binds at or close to the QB site in competition with PQ binding, although recent evidence suggests that there may be two herbicide binding sites in the Reaction Core (Hsu et al 1986, Giardi ,et al 1988, Vasil'ev et al 1988).…”
Section: The Two-electron Quinone Gate Q~mentioning
confidence: 99%
“…The contribution of photoelectrons from MC to nitrogen fixation and assimilation was validated by adding silver nitrate (AgNO 3 , an electron scavenger) to cell cultures. 3-(3,4-Dichlorophenyl)-1,1-dimethylurea (DCMU) blocks the plastoquinone binding site of PSII, preventing electron flow from PSII to plastoquinone . In the nitrogenase system, the Fe protein cycle involves a transient association between the reduced, MgATP-bound Fe protein and the MoFe protein and includes electron transfer, ATP hydrolysis, the release of Pi, and the dissociation of the oxidized, MgADP-bound Fe protein from the MoFe protein. , MgATP hydrolysis has been proposed to be absolutely required for electron transfer from the Fe protein to the MoFe protein.…”
Section: Methodsmentioning
confidence: 99%